Romániából repatriált oroszok letelepítése a Sztavropoli Körzetben a második világháborút követően - Krjucskov, Igor (Acta Scientiarum Socialium, 2016)
The Settling of Russians Repatriated from Romania in the Stavropol region after World War II. The article reconstructs the history of the descendants of those Don Cossacks who in the 18th century, discontented of the policy of the Emperor Peter I, migrated to the Ottoman Empire including the territory of modern Romania. In 1947–1948 the Soviet government convinces these Cossacks to return to their motherland. Generally they settled in the Krasnodar and Stavropol region. Repatriates didn’t get compensation from Romania for their abandoned property, they only could count on the help of Moscow and local authorities. Repatriates had low level of culture and of professional qualification. The authorities paid much attention to socialistic education of the repatriates.